Sure, I'll be your Black friend : notes from the other side of the fist bump - Philippe, Ben (Harper, an imprint of HarperCollins Publishers, 2021)
In the biting, hilarious vein of What Doesn't Kill You Makes You Blacker and We Are Never Meeting in Real Life comes Ben Philippe's candid memoir-in-essays, chronicling a lifetime of being the Black friend in predominantly white spaces. From cheating his way out of swim tests to discovering stray family members in unlikely places, he finds the punchline in the serious while acknowledging the blunt truths of existing as a Black man in today's world.